Inclusão de crianças autistas na educação infantil: avanços e desafios da escola pública no município de Parintins-AM - Costa, Keriane Pereira da (Brasil, 2022)
This research aimed to describe the advances and challenges of autistic children who are in public Early Childhood Education in the city of Parintins-AM. In the methodological course of this investigation, the bibliographic research was used, which followed from the survey of the literature and the set of treaties and laws that regulate the inclusion of autistic children in regular schools and the field research. The bibliographic research was followed by a survey of the literature and the set of treaties and laws that regulate the inclusion of autistic children in regular schools. The subjects who participated in the research were: coordinator of inclusive education at SEMED/Parintins-AM, four (4) teachers and one (1) atypical mother. Data were collected from a letter sent to the Coordination of Inclusive Education at SEMED/Parintins, questionnaires applied to teachers and children's parents via email, WhatsApp and a printed questionnaire. The research results indicate that there is a set of national laws and international agreements that guarantee the inclusion of autistic children in regular schools, however their inclusion in public Early Childhood Education requires advances related to the communication and interaction of educators with the children's families; didactic-pedagogical planning and organization of schools; improvements in the infrastructure of educational institutions; acquisition of teaching materials and resources; continuous training of educators, a multidisciplinary team and expansion of multifunctional resource rooms in the Early Childhood Education Centers, in order to guarantee social, intellectual, physical and psychological development for children with Autism Spectrum Disorder (ASD), completing the family's action. It is hoped that this work can contribute to studies related to the inclusion of autistic children in public Early Childhood Education in the perspective of social inclusion and integral development.